Characteristics of carbon fiber for badminton gears - Yeh, J.-T.; Chen, W.-J. (IEEE Xplore, 2020)
Badminton is a popular sport for all ages. This sport is considered as one of the less environment-friendly sports due to the consumption of the shuttlecocks. To solve this problem and improve the durability of a shuttlecock, many manufacturers have developed synthetic shuttlecocks. Most of the shuttlecocks are made of plastic as skirts. Recently, carbon fiber and foam material are used for the shaft and the vane of the feather of shuttlecocks. As the flying speed of the shuttlecock is the fastest among all kinds of sports, the aerodynamic performance is mainly considered as the subject for studying the characteristics of a shuttlecock. To present the aerodynamic characteristics of a shuttlecock, a wind tunnel test is used in various research methods. Thus, besides actual badminton games for testing and comparison, this study also uses a small-size wind tunnel to collect data from natural feather and carbon fiber Shuttlecock. The results of the comparison show that the shape of the shuttlecock of carbon fiber is similar to that of the feather and completely different from that of plastic. After the actual badminton games, the durability of the carbon fiber shuttlecock proved the durability